Impact of vancomycin area under the curve in early or later phase on efficacy and nephrotoxicity in patients with enterococcal bloodstream infections: a multicenter study - Piyawadee Tangvichitrerk; Dhitiwat Changpradub; Jatapat Hemapanpairoa; Piraporn Juntanawiwat; Wichai Santimaleeworagun (BMC Infectious Diseases)
Abstract Background The optimal pharmacokinetic and pharmacodynamic (PK/PD) parameters of vancomycin that can improve outcomes in enterococcal infections remain controversial. To clarify the therapeutic target for this antibiotic, this study aimed to determine vancomycin PK/PD parameters associated with efficacy in the early (during 72 h) or later (after 72 h) phase of treatment and nephrotoxicity in enterococcal bloodstream infection patients. Methods This multicenter retrospective study reviewed medical records of patients with enterococcal bloodstream infections treated with intravenous vancomycin infusion for at least 72 h between January 2016 and March 2024 at Phramongkutklao Hospital or Nopparatrajathanee Hospital in Bangkok, and Rachaburi Hospital in Rachaburi Province, Thailand. Patients with data available on serum vancomycin concentration were analyzed. The primary outcomes were 30-day mortality and acute kidney injury. The estimates of the mean 24-h area under the curve in the first 72 h (AUC24) and in steady state (AUCss) were determined by Bayesian theorem. Results Overall, 201 vancomycin concentrations were measured within the first 72 h after vancomycin treatment, while 156 were in a steady state (> 72 h). According to Classification and Regression Tree analysis, vancomycin AUC at 420 mg﻿·h/l was the PK/PD target for 30-day mortality. Results reveal that patients with AUC24 (early phase) and AUCss < 420 mg﻿·h/l (later phase) had significantly higher 14-day, 30-day, and in-hospital mortality than AUC ≥ 420 mg﻿·h/l groups. In addition, patients with AUC24 ≥ 420 mg﻿·h/l in the early phase had significantly reduced microbiological failure (p = 0.004). Patients with AUC ≥ 700 mg﻿·h/l in early and later phases had significantly increased acute kidney injury risk. In addition, patients receiving concomitant nephrotoxic drugs had an AUC cutoff value of 650 mg﻿·h/l. Multivariate Cox regression analysis showed that vancomycin AUCss < 420 mg﻿·h/l, unknown source of bacteremia, and acute kidney injury were significantly associated with 30-day mortality. Conclusions AUC 420–650 mg﻿·h/l in early and later phases was the target of vancomycin’s PK/PD in enterococcal bacteremia patients for efficacy and to prevent acute kidney injury. This study suggests close monitoring of vancomycin levels to ensure efficacy and safety.